Headlines for Health! Clean Sweep - Joy C. Jordan; Hyun-Jeong Lee; Susan Williams; Jessica Kochert (EDIS)
4HL HE70 is a multi-part 4-H curriculum by Joy Jordan, Hyun-Jeong Lee, Susan Williams, and Jessica Kochert. A series of six lessons targeted to 5th grade youth covers hazardous household products, mold, lead, radon, air pollution, and asthma triggers. Each lesson is mapped to relevant Sunshine State Standards. Published by the UF Department of Family, Youth and Community Sciences, January 2007.